Wave-current interactions in the continental shelf bottom boundary layer of the Australian North West Shelf during tropical cyclone conditions. (1st August 2018) - Drost, Edwin J.F.; Lowe, Ryan J.; Ivey, Greg N.; Jones, Nicole L.
Abstract: The distant passage of an intense and large Category 3 Tropical Cyclone (TC) generated highly energetic surface waves in a large region across the Australian North West Shelf (NWS). Two sites on the continental shelf experienced maximum significant wave heights of up to 10 m with near-bed wave orbital velocities up to 0.7 m s −1 at 40 and 74 m depth. Concurrent current profiles were measured between 0.5 and 8.5 m above the seabed at these sites and therefore the observations presented in this study allowed a detailed analysis of the wave-current interactions in the continental shelf bottom boundary layer during highly energetic tropical cyclone conditions. These observations revealed a strong modification of the current profiles during the TC with an increase of the apparent bottom roughness by up to 2 orders of magnitude compared to the typical tide-dominated current conditions. This modification was predominantly due to wave-current interactions; however, the results also suggest that changes in bed forms during the TC conditions likely acted as a secondary mechanism contributing to the enhanced bottom roughness experienced by the mean currents. A comparison of the total mean bed shear stresses as a function of the waves and currents showed a somewhat larger enhancement due to the nonlinear wave-current interactions than predicted by common semi-empirical models. Overall, the enhancement of the mean bed shear stresses during the TC significantly reduced the mean current velocities in the bottom boundary layer, highlighting the importance of including wave-current interactions within ocean circulation models to accurately predict shelf currents during TC conditions. Highlights: Strong modification of bottom boundary layer current velocity profiles to the energetic tropical cyclone waves. Apparent roughness values increased by up to 2 orders of magnitude during the cyclone impact. Wave-current interactions were primary mechanism responsible for this bed shear stress enhancement. Changing bed forms likely acted as a secondary mechanism. Inclusion of wave-current interactions in ocean circulation models is necessary to accurately predict current velocities in the bottom boundary layer.